2000
DOI: 10.1242/jcs.113.23.4253
|View full text |Cite
|
Sign up to set email alerts
|

The genomic silencing of position-effect variegation in Drosophila melanogaster: interaction between the heterochromatin-associated proteins Su(var)3-7 and HP1

Abstract: Position-effect variegation results from mosaic silencing by chromosomal rearrangements juxtaposing euchromatin genes next to pericentric heterochromatin. An increase in the amounts of the heterochromatin-associated Su(var)3-7 and HP1 proteins augments silencing. Using the yeast two-hybrid protein interaction trap system, we have isolated HP1 using Su(var)3-7 as a bait. We have then delimited three binding sites on Su(var)3-7 for HP1. On HP1, the C-terminal moiety, including the chromo shadow domain, is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Drosophila SU(VAR)3–7 heterochromatin protein has been shown to interact with HP1 (Delattre et al ., 2000). SU(VAR)3–9 bait constructs and SU(VAR)3–7 prey constructs were tested for interaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Drosophila SU(VAR)3–7 heterochromatin protein has been shown to interact with HP1 (Delattre et al ., 2000). SU(VAR)3–9 bait constructs and SU(VAR)3–7 prey constructs were tested for interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The bait constructs 1–188 and 81–188 were prepared by a Sal I self‐ligation of clones 1–569 and 81–635, respectively. HP1 and SU(VAR)3–7 bait and target constructs are described in Delattre et al . (2000), and were kindly provided by P.Spierer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HP1a is also modestly enriched along the male X [ 124 , 125 , 126 ]. The morphology of the polytene male X chromosome is similarly affected by reduction of Su(var)3-9 and by reduction or overexpression of Su(var)3-7, a heterochromatin protein that interacts with HP1a and Su(var)3-9 [ 107 , 108 , 127 ]. The bloated X phenotype of Su(var)3-7 or Su(var)3-9 mutants is rescued by mutations in MSL complex members, revealing a genetic interaction with dosage compensation [ 107 ].…”
Section: Heterochromatin and The Male X Chromosomementioning
confidence: 99%
“…All members contain two conserved domains: the chromodomain and the chromo shadow domain, the latter being involved in interaction with protein partners (Aasland and Stewart, 1995; Koonin et al ., 1995). In Drosophila , we have shown that HP1 interacts with another heterochromatin‐associated modifier of variegation, Su(var)3‐7 (Cléard et al ., 1997; Delattre et al ., 2000). Drosophila HP1 also interacts with origin recognition complex (ORC) proteins and co‐localizes with the Arp4 protein in pericentric heterochromatin (Frankel et al ., 1997; Pak et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%